1881 Wash. Sess. Laws 121-22, An Act to Incorporate the City of Port Townsend, ch. 2, § 21. - (:unkn) unknown (My University, 1881)
The City of Port Townsend has power to prevent injury or annoyance from anything dangerous, offensive, or unhealthy, and . . . to regulate the transportation and keeping of gunpowder, or other combustibles, and to provide or license magazines for the same[.]
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER